Studying the Behavior of Avoiding Cultural and Social Information of Students and Presenting a Model - Mohsen Shirazi Mehrabad; Afshin Mousavi Chelak,; Maryam Salami,; Soraya Ziaei, (کتابداری و اطلاع‌رسانی)
Objective: Despite the production and organization of a lot of cultural and social information in the country, students avoid this information. The purpose of this research was to identify the causes and factors of avoiding this type of information among the country's students and also to design a theoretical model of information avoidance behavior. It is cultural and social information among students.Methodology: This qualitative research was conducted using the grounded theory approach. It was done with detailed semi-structured interview method. The samples included 12 students in different academic levels of the country's universities. In the sampling, we tried to select students who have a brief knowledge of cultural and social information. The data of the six components were extracted during three stages of coding from interviews, open coding, axial coding, and selective coding with the help of MaxQDA software version 2020.Findings: 526 primary codes were extracted from the open coding, 77 codes were extracted from the axial coding, and 23 core categories were extracted from the selective coding. In the final model, the causal conditions of avoiding scientific and cultural information were: cognitive causes, psychological casual skill, cultural and social causes and invasive causes. Also, resource infrastructure, political factors, socio-cultural factors, environmental factors of the university, information system, educational system, and the attitude and approaches of the university are the interfering conditions of this information behavior. The background conditions of this information behavior were: background knowledge of information, background knowledge of the person, nature and characteristics of information and information source, information models and policies, and the cost of information. And favoring intellectual and intellectual information and disfavoring instinctive information, helping comprehensive growth and preventing one-dimensional growth and development of students, increasing comprehensive analysis of the state of oneself and the country, cultural and social development of students, cultural self-confidence and lack of orientation towards culture It was alien to the strategies resulting from this interview.Conclusion: Considering the impact of cultural and social information on the growth and development of students and the prevalence of information avoidance behavior among students, by knowing this behavior and coping strategies, the harms and negative effects of this behavior can be created with factors such as explaining the value of cultural information. The feeling of need to this type of information, reforming the educational system, and preventing the one-dimensional growth of students can be reduced by requiring the consumption of cultural data, improving the quality of information and the information platform (information system), and removing behavioral inertia against the flow of cultural information.